Cell dynamics in cervical loop epithelium during transition from crown to root: implications for Hertwig's epithelial root sheath formation. (14th September 2012) - Sakano, M.; Otsu, K.; Fujiwara, N.; Fukumoto, S.; Yamada, A.; Harada, H.
<x xml:space="preserve">Abstract</x> Background and Objective Some clinical cases of hypoplastic tooth root are congenital. Because the formation of Hertwig's epithelial root sheath (HERS) is an important event for root development and growth, we have considered that understanding the HERS developmental mechanism contributes to elucidate the causal factors of the disease. To find integrant factors and phenomenon for HERS development and growth, we studied the proliferation and mobility of the cervical loop (CL). Material and Methods We observed the cell movement of CL by the DiI labeling and organ culture system. To examine cell proliferation, we carried out immunostaining of CL and HERS using anti‐Ki67 antibody. Cell motility in CL was observed by tooth germ slice organ culture using green fluorescent protein mouse. We also examined the expression of paxillin associated with cell movement. Results Imaging using DiI labeling showed that, at the apex of CL, the epithelium elongated in tandem with the growth of outer enamel epithelium (OEE). Cell proliferation assay using Ki67 immunostaining showed that OEE divided more actively than inner enamel epithelium (IEE) at the onset of HERS formation. Live imaging suggested that mobility of the OEE and cells in the apex of CL were more active than in IEE. The expression of paxillin was observed strongly in OEE and the apex of CL. Conclusion The more active growth and movement of OEE cells contributed to HERS formation after reduction of the growth of IEE. The expression pattern of paxillin was involved in the active movement of OEE and HERS. The results will contribute to understand the HERS formation mechanism and elucidate the cause of anomaly root.